The Role Of Information Technology In Improving The Competitiveness Of Small And SME Enterprises - Hasanah, Ananda Uswatun; Shino, Yamato; Kosasih, Sandy (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2022)
Small and Medium Enterprises (SMEs) play an important role in the economic and industrial growth of a country. Almost 90% of all activities in the world are contributed by SMEs. In addition, SMEs contribute to employment. Empirical studies show that SMEs internationally are a source of job creation so that the contribution of SMEs to employment in both developed and developing countries, including Indonesia, plays an important role in overcoming unemployment. Problems in the current era of the global economy, SMEs must make changes to increase their competitiveness. One of the important factors that will determine the competitiveness of SMEs is information technology (IT). Therefore, the purpose of this research is to use Information Technology for novelty that can improve business transformation through the speed, accuracy, and efficiency of exchanging large amounts of information. The European case study also shows that more than 50% of productivity is achieved through investment in information technology. SMEs are said to be globally competitive if they can carry out their business activities in a reliable, balanced and high quality manner.